Alternative Dispute Resolution (ADR) Sebagai Penyelesaian Sengketa Non Litigas - Yunari, Afrik (INOVATIF: Jurnal Penelitian Pendidikan, Agama dan Kebudayaan, 2016)
In Indonesia the settlement of disputes in the business world, such as in trade, banking, mining projects, infrastructure and so on is done through a litigation process that is the process of dispute resolution between the parties conducted in court. But since the passing of Law number. 30 of 1999 on Arbitration and Alternative Dispute Resolution commonly known as Alternative Dispute Resolution (ADR), dispute resolution can be done with non-litigation path that is the dispute resolution outside the court. In the law, it is stated that alternative settlement of disputes outside the court can be done by using methods of consultation, negotiation, mediation, conciliation, or expert judgment. Alternative types of dispute resolution can be chosen by both business people and the public at large to resolve their civil disputes. ADR arises because of the demands of the business world to resolve disputes in simple, quick, and light costs. Although ADR is not considered to be a substitute for dispute resolution mechanisms through litigation, ADR is the answer of legal practitioners who have critical views of the justice system, such as the length of a litigation process in court to achieve final binding, judicial corruption, which is open to the public, the rise of case brokers, and others. Therefore, this paper will discuss Alternative Dispute Resolution (ADR) as a non litigation dispute option.